Osmotic dehydration of mackerel (Scomber Japonicus) fillets by means of binary and ternary solutions - Agustinelli, Silvina Paola (2015)
Osmotic dehydration of mackerel fillets was achieved by immersing them in binary and ternary solutions (NaCl/water or NaCl/sucrose/water). The kinetics of water loss and NaCl and sucrose gains were studied, as well as the accuracy of empirical models to explain these experimental behaviours. The results show how the presence of both solutes can enhance water loss and also interfere in each other’s diffusion. Among the three empirical models analyzed, Peleg’s equation proves to be the most suitable (R2>0.836) to describe all the mass transfer process. A modified Peleg’s model was also obtained with a high performance to describe the relationship between water content of mackerel fillets and sucrose and NaCl concentration in binary and ternary solutions.